Securing the Metaverse: AI-Driven Solutions for Cyber Security, Privacy, and User Trust - Premanand Narasimhan; Dr.N.Kala (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The Metaverse, an evolving digital landscape where users engage in immersive experiences, presents new opportunities for cybercriminals, leading to a rise in various cybercrimes. This abstract examines the nature of cybercrime within the Metaverse, focusing on prevalent offenses such as identity theft, harassment, and virtual asset theft. As interactions and transactions increasingly shift to these virtual environments, the need for robust security measures becomes paramount. The anonymity inherent in the Metaverse complicates the identification of both victims and perpetrators, necessitating innovative regulatory frameworks and international collaboration to effectively combat these crimes. This study explores the motivations behind cybercriminal behavior in the Metaverse and evaluates the effectiveness of existing legal frameworks. It also proposes comprehensive strategies for enhancing security, including the use of artificial intelligence for threat detection, the development of strong cyber laws, and educational initiatives to equip users with the knowledge to navigate these environments safely. Ultimately, understanding the dynamics of cybercrime in the Metaverse is essential for protecting users and ensuring the integrity of this emerging digital space. By fostering collaboration among stakeholders, including law enforcement, platform developers, and users, the research aims to establish best practices for mitigating risks and promoting a safer virtual environment.